Two new troglobitic species of Pseudochthonius Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from Southeastern Brazil - Guimarães, Lucas; Prado, Guilherme C.; Ferreira, Rodrigo L. (Zootaxa, 2025)
Two new troglobitic species of pseudoscorpions from the genus Pseudochthonius are described from Minas Gerais, southeast of Brazil. Detailed morphological descriptions, diagnostic characteristics, and illustrations are provided for Pseudochthonius maquinensis sp. nov. and Pseudochthonius urubuquaqua sp. nov. Additionally, we discuss and suggest future research directions, highlighting the importance of cave conservation for the protection of these newly described species. We also emphasize the need for further exploration in uncharted areas, as it is likely that additional new species will be discovered. Lastly, we include a habitat description for the newly described species and present a key for distinguishing the Pseudochthonius species recorded in Brazil.